Conceptual synergetic geological and hydrogeological model of suffusion and karst development in carbonate rocks on the territory of Svyatogirsk monastery - Суярко, В. Г.; Сухов, В. В. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2015)
Causes of geodynamic processes of suffusion and karst formation in carbonate rocks have been considered. It has been determined that the main factor in their formation is groundwater with different origins and directions. Their filtering in the array of loamy-Cretaceous rocks is provided by three systems of cracks – exogenous (weathering), lithogenic (diagenetic) and tectogenous. It is shown that suffusion processes that are the result of mechanical activity of groundwater, take place in parallel with the processes of karst formation due to chemical interaction of the components of "rock - water" with different genesis in carbon dioxide. According to the results of isotopic analysis of carbon heavy isotopes in minerals it has been found out that its genesis in epikarst products meets atmospheric, and the matter of aragonite tectonic cracks – depth genesis. A conceptual synergistic spatial geological and hydrogeological model of suffusion and karst formation in rocks of Upper Cretaceous carbonate "chalk rock" has been built for the first time on which the historical and architectural monuments of Svyatogirsk monastery stand. This model allows to determine possible geological risks to monastic buildings and develop a method to protect them from destructive geodynamic processes.